Cultural Human Rights and the Problems of their Implementation in the Modern World - BIRMANOVA, Aksunkar I.; KOZHAKHMETOV, Galym; KAKIMOVA, Maira Sh. (Journal of Advanced Research in Law and Economics; Vol 9 No 5 (2018): JARLE Volume IX Issue 5(35) Fall 2018, 2018)
Modern globalization processes cause the transformation of the substantive aspect of human rights, which requires their scientific substantiation. The article is devoted to the theoretical and methodological analysis of cultural human rights, as well as the problems of their realization in the modern world under the influence of socio-economic, political and spiritual modifications. As a result of the study, the axiological importance of implementation of person’s cultural rights has been proved and the interrelation with other, no less important, human rights has been shown; factors of an objective and subjective nature that impede the protection and realization of cultural human rights are established. The comparative legal analysis of constitutional propositions, national laws and international legal acts in the sphere of recognition and realization of cultural rights made it possible to reveal the reform trends in their legal regulation in the democratic states of the world. Given the lack of a unified doctrinal paradigm of understanding cultural rights, the adoption of a universal strategic international legal act aimed at promoting the realization of cultural human rights in the modern world – the ‘International Action Plan for Developing an Effective Mechanism for the Implementation of Cultural Human Rights in the age of Globalization’ was proposed at the international level.